Manner-of-speaking in a corpus-based translation study of narrative texts - Molés-Cases, Teresa (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This contribution examines manner-of-speaking (e.g. murmur, mutter) in a German>Spanish parallel corpus of narrative texts. This research was prompted by the fact that this phenomenon had not yet been paid due attention in the “Thinking-for-Translating” framework, in comparison with the phenomenon of manner-of-motion (e.g. limp, run). The starting point of this paper is thus the widely confirmed fact that, in previous works focusing on the translation of manner-of-motion between languages belonging to different typologies, some alterations regarding manner have been identified (e.g. omission, addition), and that this is mainly due to typological differences between source and target language. More precisely, speakers of satellite-framed languages (including German) often encode manner, while users of verb-framed languages (including Spanish) usually devote more attention to the lexicalization of path, sometimes at the expense of manner. Thus the aim of this paper is twofold: first, to examine translators’ behaviour regarding manner-of-speaking in a satellite-framed language>verb-framed language translation scenario (German>Spanish), specifically focusing on the translation of reporting verbs in a corpus of narrative texts; second, to compare the resulting data with findings from previous comparable studies dealing with the communication and motion frames. In the translation scenario studied here, the results suggest that translator behaviour differs when dealing with these two frames: while manner-of-motion is often omitted in translations into Spanish (from German), manner-of-speaking is usually transferred, or even added.